Ekstraksi Fitur Kupu-Kupu Menggunakan GLCM, Lacunarity, HSV, dan MLP - Rahayu, Putri Nur; Annisa, Aulia Rahma; Ardiana, Mirza; Andika, Yudi; Rakhmadi, Ardhon (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2025)
Extraction feature in butterflies are using GLCM, Lacunarity, and HSV. The combination of extraction feature is to improve accuration of butterflies. In this research , there are three steps for extraction. First step is extraction with GLCM and lacunarity for extraction texture, and HSV for extraction color, the second step is classification with MLP.